Забезпечення неперервного моніторингу процесів модернізації організування виробничої діяльності приладобудівних підприємств - Петрович, Й. М.; Савоніна, Н. С.; Petrovych, Yo.; Savonina, N. (Видавництво Львівської політехніки, 2017)
Розроблено алгоритм моніторингу результативності процесу модернізації організування виробничої діяльності приладобудівного підприємства та описано шляхи його реалізації, що забезпечує достовірність і адекватність отримуваної оцінки ре- зультативності процесу модернізації на підприємстві та може бути важливим інструментом її оперативного контролю і планування коригувальних дій. Для моні- торингу результативності процесу модернізації організування виробничої діяльності приладобудівного підприємства запропоновано використовувати «Індекс модернізації організування виробничої діяльності», що формується на основі виробничої функції з використанням розрахованих вагових коефіцієнтів та коефіцієнтів організування виробничої діяльності за основними виробничими чинниками.

To achieve the goals and tasks of modernizing the organization of production activities, it is advisable to monitor its effectiveness. In the process of managing the entire enterprise, or a separate structural subdivision, there are large number of unforeseen procedures for managing situations and uncertainties. Decision-making in emerging situations largely depends on the system of process monitoring, which gives grounds for making conclusions about the correctness of the decision in a particular situation. Existing evaluation methods today can be described by one algorithm. An algorithm for monitoring the effectiveness of the process of modernizing the organization of the production activity of the instrument making enterprise is described, and the ways of its implementation are described, which ensures the reliability and adequacy of the received assessment of the effectiveness of the modernization process at the enterprise and can be an important tool for its operational control and planning of corrective actions. The model of monitoring of the effectiveness of the process of modernization of the organization of the production activity of the device-making enterprise proposed in this paper is based on the use of the production function of the Cobb-Douglas. To monitor the effectiveness of the process of modernizing the organization of the production activity of the instrument making enterprise, it is proposed to use the "Index of modernization of the organization of production activity", which is formed on the basis of the production function, using the calculated weighting coefficients and the coefficients of organizing the production activity by the main production factors. The use of the process approach allows monitoring and measurement to be made, to determine the state of the enterprise's production activity at the moment, and to predict its future status. At the same time, monitoring should provide justification, and measurements in the monitoring process should ensure the reliability of the results.
Providing non-external monitoring of modernization organization of manufacturing of applied construction enterprises
Keywords: модернізація; моніторинг; ефективність модернізації; modernization; monitoring; efficiency of modernization; 338.3; 330.3